2005
DOI: 10.1258/0022215054797934
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid otorhinorrhoea due to inner-ear malformations: clinical presentation and new perspectives in management

Abstract: Children presenting with recurrent meningitis and CSF rhinorrhoea should be investigated for congenital inner-ear anomalies. In these cases CSF fistulae should be repaired using fibrin or cyanoacrylate glue and intra-operative continuous lumbar drainage; 3D FSE T2WI and 3D FIESTA MRI sequences of the inner ear are helpful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 10 publications
1
27
0
Order By: Relevance
“…In some instances where insufficient data were presented in the manuscript to categorize cases adequately, the authors were contacted and asked to provide the missing details. Publications with substantial remaining uncertainties or insufficient details were not included (71,89,182,200,207,213).…”
Section: Search Strategy and Resultsmentioning
confidence: 99%
“…In some instances where insufficient data were presented in the manuscript to categorize cases adequately, the authors were contacted and asked to provide the missing details. Publications with substantial remaining uncertainties or insufficient details were not included (71,89,182,200,207,213).…”
Section: Search Strategy and Resultsmentioning
confidence: 99%
“…However, with malformed ears, particularly in cases with severe inner ear malformations of IP-Type I and common cavity, greater CSF pressure acts on the media wall of the middle ear because of fundus deficiency as well as lack of modulus [8,17,32]. Therefore, with the classical stapedectomy approach, i.e., packing the CSF leakage through the oval window direction from middle ear cavity to the vestibule, several previous studies have indicated various recurrence rates due to packing materials not being strong enough to withstand the high-pressure of CSF, even CSF drainage and post-operation medication were used [12,16,18]. Wetmore et al showed that 54% (30/56) cases of childhood CSF otorrhea had undergone an average of three operations most of which were stapedectomy with packing of the vestibule with muscle graft [3].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, to strengthen the stability of the packing materials, and reduce recurrent of CSF otorrhea, revised techniques of stapedectomy approach were reported [11,18,24]. For example, Wilson et al [11] performed blind sac closure of the external auditory canal to obtain a vigorous obliteration of the Eustachian tube and middle ear cavity, whereas, Stevenson et al [24] placed grafts around the stapes footplate to prevent the possibility of a CSF gusher, particularly in case of severe inner ear malformation.…”
Section: Insertmentioning
confidence: 99%
See 2 more Smart Citations